Prevalencia de las enfermedades de la infancia en niños y niñas menores de 5 años del servicio de pediatría del hospital Julius Doepfner del cantón Zamora. Periodo 2014. - Kayap Wisum, July Lisbeth (2016)
The present investigation work had as purpose to determine Prevalencia of the illnesses of the childhood in children and girls smaller than 5 years of the service of pediatrics of the hospital Julius Doepfner of the canton Zamora. Period 2014, the technique that was used was the observation with the observation guide, the descriptive, bibliographical, traverse, retrospective method was used, of field and by means of the realization of the investigation he/she gave the following thing as a result: The prevalencia in general of the illnesses Prevalentes of the childhood was of the 20,63, the main illnesses Prevalentes of the childhood was ANGER (Breathing Sharp Infections) with 65,21%, followed by EDA (Illnesses Sharp Diarreicas) with 21,74%, the main factors of risk were the age one year (smaller Nursling) with 54,35%, of feminine gender with 52,17%, of urban residence with 78,26%, of mestizo ethnos with 91,30% and of entrance half relative with 43,48%, previous to this the author carries out an action plan guided to the promotion and prevention of the illnesses of the childhood inclination of qualifications also directed family Parents, educating mothers and public employees of CIBV Bombuscaro, she was carried out domiciliary visits to children that entered to the pediatrics service in the year 2014. Finishing this form that the ANGER is the main illness prevalente of the childhood.